ANTHROPOMETRICAL STATUS AND GENDER DIFFERENCES AT 12 YEARS OF AGE - Ilir Gllareva (Sport Mont, 2015)
The aim of this study is to verify the current anthropometrical status of the pupils of the age 12, as well as to compare it with the standards of raising in accordance with the WHO standards. In the study were included 62 pupils (42 male and 20 female). The anthropometric tests were done in height, weight, biacromial and elbow breadth, subcutaneous adipose tissue at the : suprailiac skinfold; subscapular skinfold; triceps skinfold, as well as the abdominal circumference. The results showed that there was a heterogenic distribution of results, especially in the body weight, where the distribution between the minimal and maximal results is 28-70 kg, with the average 43, 14 ± 9, 78 of standard deviation with the male pupils, while with the female pupils was noticed more homogenous group and the standard deviation was significantly lower than with the female pupils in all variables. The findings show that almost in all measured variables female pupils are more developed at this age, especially the body high, body weight and subcutaneous adipose tissue, while as regards the abdominal circumference and body breadth, the male pupils are more developed. Comparison of symbolic sample of this research with the WHO data shows an approximate trend of raising and development of children which were included in this research, and the difference is as follows: Female pupils age 12, body height=151.97 cm